Downstream of Leading Primary Sector Industries in Papua Island - Manda’ Sarungallo; Albertus Girik Alo; Roni Bawole (Universitas Udayana, 2025)
The downstream policy for several industries in Indonesia is articulated in the 2020-2024 RPJMN, which outlines plans for each area to develop leading commodities. This study aims to determine the predominant industries downstream of the primary sector in Papua Island. This study utilizes the 2016 Indonesian Inter-Regional Input Output (IRIO) Table issued by the Central Statistics Agency (BPS) as its data and models. The primary industries can be determined by computing the backward linkage index and the forward linkage index. The study's findings indicate that the predominant sector in Papua Island is the fisheries industry. The analysis reveals that the fisheries sector possesses both backward and forward linkage indices exceeding one. This signifies that the fishing sector significantly influences the advancement of other businesses that utilize its products as inputs. The fisheries business extensively employs outputs from various other industries as inputs for its operations.